The Augmented reality with Marker Based Tracking for Introduction to Hydroponics: Augmented reality with Marker Based Tracking for Introduction to Hydroponics (PETIR, 2023)
This research explains the implementation of Augmented Reality (AR) technology with Marker Based Tracking method in the hydroponic recognition system at Pesantren Nurul Huda. This system can assist students in the learning process about the maintenance of hydroponic plants by adding visual and interactive information to the hydroponic plants in the pesantren. In addition, this system can also assist in the management of hydroponic plants by adding features for monitoring the condition of the plants and providing appropriate care recommendations. The results of this research are expected to increase students' interest in agriculture and help in the management of hydroponic plants at Pesantren Nurul Huda. Augmented Reality (AR) can be implemented based on image or picture detection, commonly known as Marker Based Tracking method. By pointing the camera towards the printed image or marker. AR can be applied in 3D hydroponic plant learning system by displaying objects such as types of plants, systems, and growing media. The marker will be detected by the camera and display 3D objects of hydroponic plants, systems, and growing media so that the hydroponic object can be observed in reality. The multimedia development uses Blender and Unity 3D. Keywords: Augmented realit , Marker Based Tracking, Hydroponics